2014
DOI: 10.1177/0194599814522765
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Biofilms and Increased Bacterial Counts Are Associated with Airway Stenosis

Abstract: Bacterial biofilms, increased bacterial counts, and higher expression of TGF-β1 and SMAD3 are associated with airway stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…In addition, other methods of assessing biofilms include standard microbiological techniques such as measuring colony‐forming units, 16s RNA sequencing, crystal violet staining, and metagenomic shotgun sequencing. Mazhar et al also reported in a study of 12 patients with and without LTS that bacterial biofilms were observed via SEM on samples of granulation tissue from all patients with LTS, whereas none were noted on normal tissue . The advantages of using metagenomic shotgun sequencing for bacterial quantification is that it can detect nonculturable bacteria and allows for actual bacteria counts from the substrate itself rather than having to incubate the bacteria in a nutrient broth or agar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other methods of assessing biofilms include standard microbiological techniques such as measuring colony‐forming units, 16s RNA sequencing, crystal violet staining, and metagenomic shotgun sequencing. Mazhar et al also reported in a study of 12 patients with and without LTS that bacterial biofilms were observed via SEM on samples of granulation tissue from all patients with LTS, whereas none were noted on normal tissue . The advantages of using metagenomic shotgun sequencing for bacterial quantification is that it can detect nonculturable bacteria and allows for actual bacteria counts from the substrate itself rather than having to incubate the bacteria in a nutrient broth or agar.…”
Section: Discussionmentioning
confidence: 99%
“…Mazhar et al also reported in a study of 12 patients with and without LTS that bacterial biofilms were observed via SEM on samples of granulation tissue from all patients with LTS, whereas none were noted on normal tissue. 27 The advantages of using metagenomic shotgun sequencing for bacterial quantification is that it can detect nonculturable bacteria and allows for actual bacteria counts from the substrate itself rather than having to incubate the bacteria in a nutrient broth or agar. This lends itself as a technique that can allow for earlier detection of bacterial load compared to that of standard culture techniques, resulting in earlier treatment of disease processes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the presence of bacterial biofilms, bacterial counts, as well as TGF-β1 protein levels are associated with the pathogenesis of benign TS, 45 and antibiotics may help prevent TS after tracheal injury. 39 PEN is a β-lactam antibiotic with high efficiency, low toxicity, and wide clinical application.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Factors that reportedly influence the incidence and development of TS include the timing and mode of mechanical ventilation after intubation, 6 mucosal injury by balloon pressure, 7 and recurrent respiratory infection. 8 …”
Section: Introductionmentioning
confidence: 99%
“…Biofilms are ubiquitous and their ability to cause persistent bacterial loads within wound beds is well‐documented. For instance, in the head and neck alone, biofilms are at least partially implicated in the pathogenesis and persistence of chronic rhinosinusitis , chronic otitis media , laryngotracheal disease , soft tissue, and mucosal infection (often after radiation, i.e., osteoradionecrosis) , and prosthetic devices, such as tracheostomy and tympanostomy tubes . To illustrate the clinical and economic burden of chronic head and neck infections, the estimated annual national inpatient cost for odontogenic infections exceeds $200 million, with one study quoting care for a cohort of 71 patients amounting to $1.1 million , while chronic rhinosinusitis accounts for more than 20 million physician visits $4 billion in healthcare expenditures per year .…”
Section: Discussionmentioning
confidence: 99%